Successful isolation of Leishmania infantum from Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) collected from naturally infected dogs - Medeiros-Silva, Viviane (2015)
Universidade de Brasília. Programa de Pós-Graduação em Medicina Tropical. Brasília, DF, Brazil.